2012
DOI: 10.1177/1012690212461632
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s just superstition I suppose … I’ve always done something on game day’: The construction of everyday life on a university basketball team

Abstract: Cherrington, Jim. 'It's just superstition I suppose … I've always done something on game day': The construction of everyday life on a university basketball team'. International Review for the Sociology of Sport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Packing of kit bag, listening music, particular kind of kit to be worn during the game etc. are few common superstitious rituals used by the athletes from long past (Cherrington, 2014). The superstitious behavior or rituals differ on the basis of nature of sports.…”
Section: Introductionmentioning
confidence: 99%
“…Packing of kit bag, listening music, particular kind of kit to be worn during the game etc. are few common superstitious rituals used by the athletes from long past (Cherrington, 2014). The superstitious behavior or rituals differ on the basis of nature of sports.…”
Section: Introductionmentioning
confidence: 99%
“…No significant difference was seen in performance when engaging in Pre-performance rituals and superstitions, when the athletes' familiarity with the sport and practise increases. One of the participant in the study conducted by Cherrington [6] reported packing his bag, listening to hip hop music and choosing the kit to be worn during the game as a pre-game ritual, which has been developed and strengthened over time. In such situations, these superstitions, for example lucky charms, provide them the assurance that they have given their best in the game.…”
Section: Introductionmentioning
confidence: 99%
“…Gregory and Petrie [13] distinguished sport superstitions from general superstitions, on the basis of the nature of superstition, under the sub-categories of equipment, uniform, clothes, routine, spectators, religion, numbers, hair, hands, charms, coins and food. Becker [14] had perhaps made the most collaborative attempt to categorize sport superstitions or at least locate them in logical groups which include (1) clothing, (2) manner of dressing, (3) numbers, (4) practices to prevent or cure injury, (5) equipment care and use, (6) practices before and during contests, and (7) omens, premonitions and beliefs about the result of a contest. Borrowed articles, new clothing was seen to disrupt an athlete's performance.…”
Section: Introductionmentioning
confidence: 99%